Effectiveness of switching between TNF inhibitors in patients with axial spondyloarthritis - Manica, Santiago Rodrigues (2020)
57763]. AS is supported by a doctoral grant from “Fundação para a Ciência e Tecnologia” (SFRH/BD/108246/2015).